The Concept of Space and its Measurement in Regional Studies - Nematollah Akabari (فصلنامه پژوهش‌های اقتصادی ایران, 2005)
A large number of regional studies are now using data empirically on different dimensions of location (contiguity, distance), which are particularly concerned with the concept of "space". This concept explains basically the interaction between human being and environment. It is, therefore, important to measure its effects on various socio-economic and regional indicators such as growth and local employment. Failure to consider the concept of "space" in the relevant empirical studies can generate biased results in estimation and prediction. The objective of the present paper is first to study the conceptual issues and different views of "space", and then to explore its impact on data that have locational aspects. The paper will particularly focus on measuring spatial effects and different quantitative techniques used in spatial econometric models.